Answer:
18 years
Step-by-step explanation:
2(8+x) = 34+x
16+2x = 34+x
-18 = -x
Answer:
![-2x^{2} -7x-6](https://tex.z-dn.net/?f=-2x%5E%7B2%7D%20-7x-6)
Step-by-step explanation:
(2x + 3) (-x - 2)
distribute first term, to the second term:
2x(-x) + 2x(-2) + 3(-x) + 3(-2)
multiply:
+ (-4x) + (-3x) + (-6)
![-2x^{2} -4x-3x-6](https://tex.z-dn.net/?f=-2x%5E%7B2%7D%20-4x-3x-6)
combine the like terms:
- 4x - 3x - 6
-7x
- 7x - 6
final answer :
- 7x - 6
hope this helped !!
mark me brainliest :D
Answer:
7
Step-by-step explanation:
The volume of the prism:
V = L x W x H,
where L is the length, W the width and H the height.
We can find the volume of the entire figure by adding together the volumes of two smaller figures ( 2 prisms ).
The 1st one has dimensions: 2, 2, 7 and the 2nd has dimensions 2, 3, 8.
Answer:
B . ( 2 x 2 x 7 ) + ( 2 x 3 x 8 )